Quality Assessment of Soaps Produced from Palm Bunch Ash-Derived Alkali and Coconut Oil - HO Ogunsuyi; CA Akinnawo (Journal of Applied Sciences and Environmental Management)
The making of soap using vegetable matter (palm bunch waste) was examined. All the factors that impact blackish on the soap products after saponification process were studied with a view to remedying them. The remedial process involved subjecting the dried palm bunch matter to total combustion, soaking, filtering and recrystallizing the ash-residue to obtain a colourless filtrate and pure extract of the alkali. Coconut oil was extracted from coconut seeds using hot –water extraction process. Soaps were produced using both the conventional and modified methods. Conventional saponification process was modified to improve on the quality of the soap produced with the extracted alkali hence, generating a neater soap which was milky in appearance. The following parameters were determined: free alkali content, total fatty matter, moisture content, lathering ability, cleansing power, matter insoluble in water, matter insoluble in ethanol. The free caustic alkali content of the black soap produced through the conventional method was found to be 0.09%, while 0.26% and 0.98% were recorded respectively for the improved and synthetic-alkali soaps. The total fatty matter content of the black soap was 55.45%, which was over two folds of 23.00% and 21.69% observed in the improved and synthetic –alkali soaps. Moisture content of modified soap was 29.05%, which was remarkably higher than 9.53% recorded for black soap and 6.65 for the synthetic-alkali soap. The lathering ability was found to be 5.00ml for black soap and 15.00ml and 10.00mL for the other soaps. The improved soap produced with purified palm bunch ash-derived alkali was comparatively of a better quality than its conventional black soap counterpart considering some physico-chemical properties such as matter insoluble in water, matter insoluble in ethanol, unsaponified neutral fat and lathering characteristics of the soaps.